The Silent Revolution: The Roman Army between Polybius and Marius - Biglino, Fabrizio (Sapiens ubique civis, 2020)
Traditionally, Polybius’ description of the Roman army in Book VI of his Histories is considered the de facto image of the mid-Republican Roman legions until the major changes introduced by the reforms attributed to Gaius Marius. However, there are several elements highlighting the fact that Polybius’ description actually depicts a rather outdated military system, making it hard to accept it as an up-to-date portrait of the army by the mid-second century. By examining hints within the sources, this paper aims to proper examine the major variations that interested the Roman military system from the mid-third to the late second centuries and to highlight their overall impact.